Statistical analysis of the physical properties and durability of water-repellent mortars made with limestone cement, natural hydraulic lime and pozzolana-lime. (1st March 2015) - Falchi, Laura; Varin, Cristiano; Toscano, Giuseppa; Zendri, Elisabetta
Highlights: Water-repellent mortars prepared using siloxanes and metal soap admixtures. Chemical–physical properties assessed before/after exposure to salt solution. Data analysed by principal component analysis and linear regression models. The relationship between the properties in different environments is evaluated by statistical methods. Abstract: Multivariate statistical methods are proposed for the analysis of the physical properties of limestone cement, natural hydraulic lime and pozzolana-lime mortars admixed with water-repellents. The relationship between the physical properties and the durability of the mortars is evaluated by principal component analysis (PCA) and linear regression models. PCA allows to visualize (i) three groups of mortars according to the binder used and the structural/mechanical properties; (ii) the durability in relation to the mortar properties in simulated conditions. Linear regression models allow to identify and quantify associations between properties, composition and durability.